MENGELOLA EMOSI MAHASISWA DALAM PEMBELAJARAN DARING MELALUI SUMBERDATA DIGITAL MASA PANDEMI COVID-19 - Bachtiar Sinuraya; Santi Virdaus Putri; Dwi Wahyuni; Desnawita Desnawita; Tri Yuliani; Meliana Sari; Refika Mastanora (IAIN Batusangkar, 2020)
This study intends to analyze and parse the management of student emotions in learning through digital sources during the Covid-19 pandemic. The family environment plays an active role in providing understanding and monitoring and paying attention to emotional states in learning. This research was conducted by analyzing literature from journals and effective data related to emotional management in online learning where the findings and new theories were described qualitatively. The results of these findings illustrate the need for the role of the tridarma of education, namely educators, students and families in managing emotions and the necessary facilities and infrastructure for students in online learning are more effective so that the education and learning process is carried out properly.